PENGARUH MEDIA CODING BLOCKLY GAMES TERHADAP KETERAMPILAN PEMECAHAN MASALAH MATEMATIKA SISWA KELAS 3 SDN PAKIS V/372 SURABAYA - Puspa Anggraini, Dilla; Roosyanti, Anna; Syehma Bahtiar, Reza (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of using Blockly Games media on students' mathematical problem-solving abilities in elementary school. The research employed a quantitative approach with a quasi-experimental design. The population consisted of elementary school students, with samples divided into experimental and control groups. Data were collected using test instruments in the form of problem-solving questions. The results showed that the use of Blockly Games media had a positive effect on students’ mathematical problem-solving abilities. This was indicated by the increase in post-test scores in the experimental group compared to the control group. Statistical analysis using the Mann-Whitney test revealed a significant difference between the two groups. Therefore, Blockly Games media can be used as an alternative learning tool to improve students' problem-solving abilities in mathematics learning.